Lichenoid mucocutaneous reactions associated with sintilimab therapy in a non-small cell lung adenocarcinoma patient: case report and review - Zhou, Shuting; Zhang, Zhenyu; Feng, Xiaodong; Zhao, Chengjian; Jiang, Lu (Frontiers in Pharmacology, 2023)
The immune checkpoint inhibitor (ICI), anti-programmed cell death receptor-1 (PD-1) antibody, has gained widespread approval for treating various malignancies. Among the immune-related adverse reactions (irAEs) during ICI treatment, the lichenoid reaction is noteworthy. Sintilimab, a new PD-1 inhibitor, has secured approval in China for treating refractory non-Hodgkin’s lymphoma, and phase I/II clinical trials for other solid tumors are ongoing both domestically and abroad. This paper presents a case of a mucocutaneous lichenoid reaction associated with sintilimab therapy, its diagnosis, and management. Our study, using multiplex immunofluorescence staining, reveals localized infiltration of CD4+ and CD8+ T lymphocytes in the subepithelial lamina propria region with upregulated PD-1 expression, implying an association between PD-1 expression upregulation and lichenoid reactions provoked by PD-1 monoclonal antibody. We provide a summary of clinical characteristics and treatment guidelines for lichenoid reactions induced by ICIs from previous reports, highlighting the success of a combined therapeutic regimen of oral antihistamines and topical corticosteroids in controlling symptoms without interrupting ICI treatment.